Investigation of Magnesium and Chromium Fillers FSW Dissimilar Joint of AA6063 and AA 5154 - Sangeetha Krishnamoorthi; M. Prabhahar; S. Prakash; L. Prabhu; K. Bhaskar; Akhil V. Suku; K. P. Shijindas; S. L. Sooraj; A. Haiter Lenin (Advances in Materials Science and Engineering)
Friction stir welding (FSW) is a solid-state metal joining process. There is no melting and recasting of metal while welding is used. Some of the defects commonly encountered in FSW are tunnel defect, bond, cracks, pin holes, and pipping defects. The defects occur because of improper metal mixing and less heat input in the weld nugget zone. In the fusion welding process, a filler rod is employed to form a quality weld with superior mechanical properties. In this work magnesium and chromium powders are used as filler materials. The purpose of this study is to ascertain whether filler materials and manufacturing processes have an impact on the weld nugget zone spot weld joint formation as well as the mechanical and abrasive properties of welded joints. This study's FSW filler materials mixing ratio and process parameters were improved by using the Central Composite Design (CCD) idea, which is discussed in more detail below Response Surface Methodology (RSM). The best empirical relationship between the parameters was provided by the CCD. The mathematical relationships were established to forecast the maximum tensile strength, maximum weld nugget hardness, and minimum corrosion rate by incorporating filler materials with process parameters. The optimal processing factors combination is predicted by conducting the validation test. The optimum parameters were the tool rotatory speed 600–1000 revolution per minute, welding speed 60 to 180 mm/min, plunge depth of 0.05 to 0.25 mm, center distance between the sample is 0–4 mm, as well as powder mixing ratio of 90 : 10, 92.5 : 7.5, 95 : 5, 97.5 : 2.5, and 100 : 0, the tensile test, microhardness, and corrosion rate analysis were conducted on the weld specimen. The welded test specimen provides better joint strength, weld nugget hardness, and enhanced corrosion resistance properties. The microstructure analysis shows the fine grain structure and homogeneous distribution of filler material with the base metal in the welded area.